Integration of Science Based on Philosophy Review (Study Aspects of Ontology, Epistemology, and Axiology) - Hayati, Nursri; Dalimunthe, Irwan Shaleh (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
This study aims to determine how the integration of science based on a review of philosophy through the study of aspects of ontology, epistemology, and Axiology. This research utilizes library research methods along with data analysis techniques like as content analysis/content analysis. The findings of this study show that the integration of Science from the point of view of Ontology shows that the study of Science concerns all that exists in the universe, both abstract and concrete, and the integration of Science from the viewpoint of Epistemology shows that religious science is obtained through the process of study and interpretation through the verses of qauliyah, whilst general science is obtained through observation and experimentation through the verses of kauniyah, both of which are equally sourced from Allah Subhaanahu Wata’ala. Epistemology demonstrates that Allah SWT provides knowledge through his guidance in the Qur'an, Hadith, and the universe. The axiology aspect illustrates that knowledge integration is intended to form a perfect human (insān kāmil), or a complete human being with breadth of insight and greatness of character; knowledge integration is also an effort of raḥmatan lil 'ālamīn.